Comparative immunohistochemical study of ki-67, p53, caspase-3 in distal colonic polyps and colorectal adenocarcinoma. - Shyskin, M. A. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. Colorectal carcinogenesis is a multistep process that begins from the normal epithelium and includes the step of adenoma formation. The question of diagnostic and prognostic value of proliferation and apoptosis markers for the distal colorectal neoplasms is still open. Objective. To compare Ki-67, p53, caspase-3 expression levels in distal colonic polyps and colorectal adenocarcinoma. Methods. Pathomorphological and immunohistochemical studies of biopsies of distal colonic polyps from 30 patients and surgical material of colorectal adenocarcinoma from 30 patients were carried out. Results. Ki-67 expression level by epitheliocytes of hyperplastic polyps is 1.5 times lower than that for adenocarcinoma [26.23 (22.16, 48.88) % vs. 41.20 (36.62, 59.42) %], but adenomas are distinguished by 1.5 times higher Ki-67 expression level in comparison with adenocarcinoma [62.40 (48.65, 76.23) % vs. 41.20 (36.62, 59.42) %]. Caspase-3 expression level by hyperplastic polyps epitheliocytes is 1.7 times lower than that for adenocarcinoma [16.99 (11.86, 39.85) CUOD vs. 28.72 (15.84, 76.71) CUOD], but caspase-3 expression level by epitheliocytes of adenomas is 1.1 times higher than that for cancer cells [31.84 (19.53, 42.34) CUOD vs. 28.72 (15, 84; 76.71) CUOD]. The maximum proliferation and apoptosis levels were revealed for high-grade [76.23 (62.36, 85.36) % and 42.34 (33.78, 65.38) CUOD] and villous [79.09 (69.12, 84.27) % and 67.88 (63.92, 71.29) CUOD] adenomas. p53 expression level by epithelial cells of hyperplastic polyps almost is 40 times lower than that for adenocarcinoma [0.00 (0.00; 1.47) % vs. 39.67 (15.69, 83.75) %], and p53 expression level by epitheliocytes of adenomas is 16.5 times lower than that for cancer cells [2.39 (1.58, 8.26) % vs. 39.67 (15.69, 83.75) %]. Conclusion. The high levels of proliferation and apoptosis of epitheliocytes characterize the polyps-precursors of colorectal carcinoma that have the biggest malignant potential. Colorectal adenocarcinoma differs by the medium p53 expression level by tumor cells.